Penanaman Nilai – Nilai Anti Korupsi Melalui Sosialisasi Pendidikan Anti Korupsi di Lingkungan SMK - Wahyu Kristiningrum; Moneca Diah Listiyaningsih; Ika Niilawati (UNIVERSITAS NGUDI WALUYO, 2023)
UU No. 30 of 2002, Article 13, states that the KPK has the authority to organize anti-corruption education programs at every level of education. Efforts to implement an anti-corruption education program were followed up by establishing cooperation between the Ministry of National Education and several educational institutions (elementary, junior high, and high school) and universities. Students will be the next generation of the nation, so they must be introduced to the application of anti-corruption educational values starting from small things: examples of daily habits that turn out to be seeds of committing acts that lead to acts of corruption without them knowing it, for example, cheating during exams, skipping classes, collecting assignments not on time, arriving late to school, and others. To cultivate anti-corruption education among students, good cooperation is needed from all parties, including educators, who must become role models for their students by being anti-corruption. The implementation of the activity was carried out at SMK Perintis 29 Ungaran using the method of implementing socialization about instilling anti-corruption values. The data collection instrument is a questionnaire. Characteristics of adolescents based on gender, mostly women (77.3%) and men (22.7%) Knowledge about instilling anti-corruption values before being given health promotion, namely that most of them are knowledgeable enough (59.09%), and after being given health promotion, most of them experienced an increase in becoming well-informed (65.91%). Instilling anti-corruption values among students is an important thing to do so that they get used to doing the right things, not against anti-corruption values. ABSTRAK UU No. 30 tahun 2002 pasal 13 menyatakan bahwa KPK memiliki kewenangan untuk menyelenggarakan program pendidikan anti korupsi pada setiap jenjang pendidikan. Upaya penyelenggaraan program pendidikan anti korupsi ditindaklanjuti dengan dilakukannya kerjasama antara Depdiknas dengan beberapa lembaga pendidikan (SD, SMP, SMA) maupun perguruan tinggi. Pelajar akan menjadi generasi penerus bangsa sehingga harus dikenalkan penerapan nilai-nilai pendidikan anti korupsi mulai dari hal-hal kecil dari contoh kebiasaan sehari-hari yang ternyata bisa menjadi bibit melakukan perbuatan yang mengarah pada perbuatan korupsi tanpa mereka menyadarinya, misalnya mencontek ketika ujian, membolos, mengumpulkan tugas tidak tepat waktu, datang terlambat ke sekolah dan lain lainnya. Untuk membudayakan pendidikan antikorupsi di kalangan pelajar, maka diperlukan kerjasama yang baik dari semua pihak termasuk pendidik untuk menjadi role model bagi siswanya dengan berprilaku antikorupsi.Pelaksanan kegiatan dilaksanakan di SMK Perintis 29 Ungaran dengan metode pelaksanaan sosialisasi tentang penanaman nilai-nilai antikorupsi. Instrumen pengumpulan data berupa kuesioner Karakteristik remaja berdasarkan jenis kelamin sebagian besar perempuan (77,3%) dan laki-laki (22,7 %.) Pengetahuan tentang penanaman nilai-nilai anti korupsi sebelum diberi promosi kesehatan yaitu sebagian besar berpengetahuan cukup (59,09%) dan setelah diberikan promosi kesehatan sebagian besar menagalami peningkatan menjadi berpengetahuan baik (65,91%). Penanaman nilai-nilai anti korupsi dikalangan pelajar merupakan hal yang penting untuk dilakukan supaya membiasakan diri agar pelajar melakukan hal-hal benar tidak bertentangan dengan nilai-nilai anti korupsi.